2008
DOI: 10.1093/toxsci/kfn027
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Contribute to Lipopolysaccharide-Induced Teratogenesis in Mice

Abstract: Lipopolysaccharide (LPS) has been associated with adverse developmental outcome, including embryonic resorption, fetal death and growth retardation, and preterm delivery. In the present study, we showed that an ip injection with LPS daily from gestational day (gd) 8 to gd 12 resulted in the incidence of external malformations. The highest incidence of malformed fetuses was observed in fetuses from dams exposed to 20 microg/kg LPS, in which 34.9% of fetuses per litter were externally malformed. In addition, 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 38 publications
1
41
0
2
Order By: Relevance
“…On the one hand, redox-sensitive signal transduction pathways are critical for developmental processes, including proliferation, differentiation, and apoptosis of human tissues, especially for placenta; on the other hand, teratogens that induce oxidative stress, such as chemical poisoning and infection, may induce teratogenesis via the misregulation of the above-mentioned pathways (46). In particular, previous studies have discovered that ROS were involved in teratogenic processes in mice treated with LPS (7,50), which is one well-recognized pathogen-associated molecular pattern (PAMP) of Gram-negative bacteria. Structures analogous to LPS have been found in T. gondii, such as glycosylphosphatidylinositols (GPI) (9,36).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, redox-sensitive signal transduction pathways are critical for developmental processes, including proliferation, differentiation, and apoptosis of human tissues, especially for placenta; on the other hand, teratogens that induce oxidative stress, such as chemical poisoning and infection, may induce teratogenesis via the misregulation of the above-mentioned pathways (46). In particular, previous studies have discovered that ROS were involved in teratogenic processes in mice treated with LPS (7,50), which is one well-recognized pathogen-associated molecular pattern (PAMP) of Gram-negative bacteria. Structures analogous to LPS have been found in T. gondii, such as glycosylphosphatidylinositols (GPI) (9,36).…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies showed that maternal LPS exposure resulted in the development of malformed fetuses in rats and golden hamsters (8)(9)(10). Recently, we showed that maternal LPS exposure from gestational day (GD) 8 to GD12 caused external malformations and skeletal abnormalities in mice (11). We and others found that maternal LPS exposure at late gestational stages led to fetal death, intrauterine growth restriction (IUGR), skeletal development retardation, and preterm delivery (12)(13)(14)(15)(16).…”
Section: Ipopolysaccharide Is a Toxic Component Of Cell Walls Inmentioning
confidence: 99%
“…В опытах продемонстри-ровано, что интраамниотическое введение ЛПС влечет за собой тяжелые последствия как для материнского организма, способствуя развитию хорионамнионита, так и для плода, вызывая повреждения центральной нерв-ной системы и формирование врожденных пороков и аномалий [33,34].…”
Section: грибково-бактериальный дисбиозunclassified
“…В связи с вероятностью формирования при эндоген-ной инфекции связанных с беременностью нарушений в системе гемостаза [27,[30][31][32][33][34], особое значение приоб-ретают эффекты энзимов на свертывающую систему крови. На сегодня доказаны их следующие эффекты: 1) снижение (нормализация) процессов агрегации тром-боцитов и эритроцитов, что обусловлено снижением концентрации тромбоксана и блокированием адгезив-ных молекул; 2) снижение концентрации провоспа-лительных белков (брадикинина, фибриногена) и др.…”
Section: грибково-бактериальный дисбиозunclassified